PENGARUH MULTI MEDIA DAN GAYA BELAJAR SISWA TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN SUKASARI 6 KOTA TANGERANG - masfupah (Amal Insani Foundation, 2023)
This study aims to determine the effect of the use of multi-media and learning styles on social studies learning outcomes of students. This research was conducted at SDN Sukasari 6 Tangerang City from January 2013 to April 2013. The population in this study was all students in class V SDN Sukasari 6 Tangerang City totaling 76 people. Whereas in determining the research sample using probability sampling where the population used as a sample is 68 people. The research method uses an experimental design by treating groups of students (treatment) using multi-media, while for the control class using image media. Data collection techniques to obtain groups of students who have a visual learning style and auditory learning style by giving a questionnaire using a Likerst scale, while to obtain data on learning outcomes using an achievement test or post test. Data analysis techniques were performed using two-way analysis of variance (Anova) with a significance level of 0.05 or 5%. The first hypothesis is that there is a difference in student social studies learning outcomes between learning using multimedia and learning using media images as stated by the results of the Turkey test Qh 20.08 ≥ Qt 3.99. The second hypothesis is that there are differences in social studies learning outcomes between students who have a visual learning style and an auditory learning style as expressed by the results of the Turkey Qh test 4.93 ≥ Qt 3.99. The third hypothesis is that there is an interaction between learning media that uses multi-media and the learning styles of students in social studies learning. Statistically, the interaction is described as F count = 4.57 ≥ Ftable = 3.99. Fourth hypothesis There is a difference in social studies learning outcomes of students who have a visual learning style who participate in learning using multimedia compared to learning using media images, statistically this effect can be expressed by the results of the Turkey test which is Qh = 8.90 > Qt = 3.06. The fifth hypothesis is that there is a difference in social studies learning outcomes of students who have an auditory learning style who participate in learning using multimedia compared to learning using media images with the Turkey test results being Qh = 12.36 > Qt = 3.06